University Students’ Coping Behaviours and Perceived Parental Depression: The Role of Hope and Implications for Counsellors - Scott, Shawna A.; Johnson, Emily M.; Hakim-Larson, Julie (Canadian Journal of Counselling and Psychotherapy, 2015)
Research has shown links between perceived parental depressive symptomology and young adults’ depressive symptoms (Rounding & Jacobson, 2013). Hope has been linked to fewer depressive symptoms and to greater adaptive coping behaviours (Chang & DeSimone, 2001). The relation between perceived parental depression, hope, and undergraduate university students’ coping behaviours was examined. Participants were 223 undergraduates (51 males, 172 females) aged 17 to 24. Beyond perceived parental depression, hope predicted higher levels of religion/spirituality, active coping, and planning, and predicted lower levels of humour and behavioural disengagement. Implications for counselling clients at risk for intergenerational depression are discussed.